2017
DOI: 10.1038/s41598-017-11468-7
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary liquorice ingestion increases blood pressure via increased volume load, elevated peripheral arterial resistance, and decreased aortic compliance

Abstract: We investigated the haemodynamic effects of two-week liquorice exposure (glycyrrhizin dose 290–370 mg/day) in 22 healthy volunteers during orthostatic challenge. Haemodynamics were recorded during passive 10-minute head-up tilt using radial pulse wave analysis, whole-body impedance cardiography, and spectral analysis of heart rate variability. Thirty age-matched healthy subjects served as controls. Liquorice ingestion elevated radial systolic (p < 0.001) and diastolic (p = 0.018) blood pressure and systemic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
1
29
0
1
Order By: Relevance
“…Previously, we found that liquorice intake for two weeks increased BP via volume expansion, elevated peripheral arterial resistance and increased large arterial stiffness [17]. We also observed reduced chronotropic response and enhanced central wave reflection in the upright posture after liquorice exposure [17].…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…Previously, we found that liquorice intake for two weeks increased BP via volume expansion, elevated peripheral arterial resistance and increased large arterial stiffness [17]. We also observed reduced chronotropic response and enhanced central wave reflection in the upright posture after liquorice exposure [17].…”
Section: Introductionsupporting
confidence: 53%
“…The study protocol (in Finnish) with an English summary have been published [18], and the CONSORT checklist is presented as supporting information (S1 CONSORT checklist). The recruitment and characteristics of the subjects in the liquorice group and the study design were reported elsewhere [17,18]. The present results originate from the same liquorice intervention from which we published results concerning liquorice-induced changes in haemodynamics in the supine position [18] and during orthostatic challenge [17].…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Specific agents such as non‐steroidal anti‐inflammatory drugs (NSAIDs) and Kanzo [liquorice] increase the circulating volume, resulting in a non‐dipping pattern and nocturnal hypertension …”
Section: Resultsmentioning
confidence: 99%